RECEPTIONS AND MEANS OF PUBLIC RELATIONS: RATIO OF A VERBAL AND NONVERBAL COMPONENT - H. P. Popova; O. V. Bondarenko (Гуманитарные и юридические исследования)
The analysis of concepts of Public relations is presented to verbal and nonverbal communication in article, means and methods of public relations taking into account verbal and nonverbal components of communication are systematized.